Lung cancer survival and stage at diagnosis in Australia, Canada, Denmark, Norway, Sweden and the UK: a population-based study, 2004–2007 - Walters, Sarah; Maringe, Camille; Coleman, Michel P; Peake, Michael D; Butler, John; Young, Nicholas; Bergström, Stefan; Hanna, Louise; Jakobsen, Erik; Kölbeck, Karl; Sundstrøm, Stein; Engholm, Gerda; et al. (Thorax, 2013)
Background The authors consider whether differences in stage at diagnosis could explain the variation in lung cancer survival between six developed countries in 2004–2007. Methods Routinely collected population-based data were obtained on all adults (15–99 years) diagnosed with lung cancer in 2004–2007 and registered in regional and national cancer registries in Australia, Canada, Denmark, Norway, Sweden and the UK. Stage data for 57 352 patients were consolidated from various classification systems. Flexible parametric hazard models on the log cumulative scale were used to estimate net survival at 1 year and the excess hazard up to 18 months after diagnosis. Results Age-standardised 1-year net survival from non-small cell lung cancer ranged from 30% (UK) to 46% (Sweden). Patients in the UK and Denmark had lower survival than elsewhere, partly because of a more adverse stage distribution. However, there were also wide international differences in stage-specific survival. Net survival from TNM stage I non-small cell lung cancer was 16% lower in the UK than in Sweden, and for TNM stage IV disease survival was 10% lower. Similar patterns were found for small cell lung cancer. Conclusions There are comparability issues when using population-based data but, even given these constraints, this study shows that, while differences in stage at diagnosis explain some of the international variation in overall lung cancer survival, wide disparities in stage-specific survival exist, suggesting that other factors are also important such as differences in treatment. Stage should be included in international cancer survival studies and the comparability of population-based data should be improved.